Hybrid E-Glass/Basalt (H-BE) Composites Confinement for Reinforced Concrete Square Columns and Development of Stress-Strain Models - Phromphat Thansirichaisree; Hisham Mohamad; Ali Ejaz; Panumas Saingam; Qudeer Hussain (My University, 2024)
Abstract This study performs an experimental and analytical framework to explore the compressive response of concrete confined with hybridized chopped glass and Basalt (H-BE) layers. The research variables comprised the strength of unconfined concrete and the quantity of H-BE layers. Results showed significant improvements in ultimate strength, ultimate strain, and ductility with H-BE confinement, up to 161% and 269% enhancement, respectively. Unconfined concrete strength inversely affected the efficiency of confinement, while the magnitude of H-BE layers had a positive influence. The maximum enhancement in ultimate strain for low, medium, and high unconfined strength types was 219%, 146%, and 111%, respectively. An analogous trend in ultimate strength was noted, demonstrating 161%, 83%, and 33% increase for low, medium, and high unconfined strength, respectively. The elastic modulus increased with the magnitude of H-BE confinement and unconfined concrete strength. The stress vs. strain response of H-BE-strengthened concrete was characterized by an initial parabolic part, which was succeeded by a linear branch with a gentler slope. Based on regression analysis, specific expressions were presented for different key points on the curve, and their efficiency was evaluated with the coefficient of determination (𝑅2) valuesexceeding 0.90. Moreover, a methodology was presented to precisely predict the complete stress vs. strain response of concrete under H-BE confinement based on the proposed expressions. The comparison between predicted and experimental curves demonstrated close agreement, validating the proposed approach.
Keywords: Ductility (Earth science); Square (algebra); Structural Behavior of Reinforced Concrete